Implementation of Online Learning Media in the Covid-19 Pandemic - Abduloh Abduloh; Mas'ud Muhammadiah; Harizahayu Harizahayu; Catur Budi Susilo; Sa'odah Saodah; Ardian Arifin (AL-ISHLAH: Jurnal Pendidikan, 2021)
This qualitative research aims to obtain an overview of the implementation of online learning in the Covid-19 Pandemic. In general, the implementation of online learning during the Covid-19 pandemic positively impacts the continuity of education in Indonesia. This research method is obtained from online observations and Scoping reviews. Literature is obtained from various databases such as Google Scholar, Scopus, Web of Science, Crossref Search. Furthermore, the literature was mapped in several parts so that 40 appropriate literature was obtained and could be used regarding teaching and learning activities in schools and the higher education environment. The study results show that online learning is currently considered adequate to replace conventional learning, but several factors related to the implementation of learning must be considered.